Characterizing energy efficiency for heterogeneous cellular networks - Nasimi, Meysam; Hashim, Fazirulhisyam; Ng, Chee Kyun (IEEE, 2012)
Energy efficiency in wireless networks, especially heterogeneous networks (HetNets) have received a lot of attention due to energy crisis and environmental protection. This emerging trend has motivated the academic and industrial world for new research area, which leads to green networks. In this paper, we provide a brief overview on those studies with an emphasis on introducing some energy efficiency metrics in HetNets such as Energy Consumption Ratio (ECR) and Energy Saving (ES). Since these metrics provide quantified information to compare and assess the efficiency of consumed energy, understanding those metrics can yield insight into the potential energy saving in HetNets. Furthermore, the assessment of potential energy conservation of both energy efficiency metrics will be carried out in different deployment strategies such as macro-micro, macro-relay and micro-relay. The obtained numerical results show that the macro-relay deployment strategy is much energy efficient compared to macro-micro and micro-relay. Therefore, it is concluded that the energy efficiency metrics can be the key measurement for the energy consumption in HetNets.